Bacterial mechanisms for Cr(VI) resistance and reduction: an overview and recent advances - Ahemad, Munees (Folia microbiologica, 2014)
Chromium pollution is increasing incessantly due to continuing industrialization. Of various oxidation states, Cr(6+) is very toxic due to its carcinogenic and mutagenic nature. It also has deleterious effects on different microorganisms as well as on plants. Many species of bacteria thriving in the Cr(6+)-contaminated environments have evolved novel strategies to cope with Cr(6+) toxicity. Generally, decreased uptake or exclusion of Cr(6+) compounds through the membranes, biosorption, and the upregulation of genes associated with oxidative stress response are some of the resistance mechanisms in bacterial cells to overcome the Cr(6+) stress. In addition, bacterial Cr(6+) reduction into Cr(3+) is also a mechanism of specific significance as it transforms toxic and mobile chromium derivatives into reduced species which are innocuous and immobile. Ecologically, the bacterial trait of reductive immobilization of Cr(6+) derivatives is of great advantage in bioremediation. The present review is an effort to underline the bacterial resistance and reducing mechanisms to Cr(6+) compounds with recent development in order to garner a broad perspective.
Keywords: Oxidative Stress; Biodegradation, Environmental; Chromium; oxidace-redukce; chrom; biodegradace; oxidační stres; Oxidation-Reduction; Bacteria